In Memoriam Janusz Mikołaj Szymański / Barbara Klein-Szymańska. - Klein-Szymańska, Barbara (1936- ).; Klein-Szymańska, Barbara (1936- ). (Drukarnia Gutenberg, 2009)
In Memoriam Janusz Mikołaj Szymański.